FROM PREPAREDNESS TO ACTION: STRENGTHENING EMPLOYEE EMERGENCY RESPONSE TROUGH FIRST AID TRAINING - Sujarwadi, Mokh; Fitriyah, Agustini; Srengenge, Gawan; Toha, Mukhammad; Zuhroidah, Ida; Prayoga, Dimas Hadi; Laili, Nadia Rohmatul; Zahra , Fatimah (Universitas Airlangga, 2026)
Introduction: Workplace accidents are a serious problem in industrial settings, particularly in high-risk production sectors such as pharmaceutical manufacturing. This community service activity aims to improve employee knowledge and skills in providing First Aid through theory-based and practical training. Methods: The training was conducted at a pharmaceutical company in East Java on August 28, 2025, and lasted 6 hours. Participants consisted of 25 employees purposively selected by company management to represent various divisions. The method used was a one-group pre-test and post-test design, utilizing a closed-ended questionnaire containing 15 multiple-choice questions to assess first aid knowledge, as well as a practical assessment to evaluate participants’ skills. The training covered basic first aid principles and focused on three core skills: basic life support, bandaging, and casualty transportation, delivered through interactive lectures and hands-on simulations using standard first aid equipment. Results: A significant improvement in both participants’ knowledge and practical skills after the training. The mean knowledge score increased from 12.36 (pre-test) to 14.27 (post-test), representing an increase of 1.95 points. Conclusion: First aid training was effective in improving both the knowledge and practical skills of employees. A notable increase in knowledge scores, along with enhanced competencies in basic life support, bandaging, and casualty transportation, indicates that the training successfully strengthened participants’ preparedness and ability to respond to emergency situations. These findings highlight the importance of integrating structured first aid training programs in the workplace to improve emergency response capacity. KEYWORDS employees; first aid; occupational safety; training; work accidents